Latin American Association for the study of the liver (ALEH) practice guidance for the diagnosis and treatment of non-alcoholic fatty liver disease - Arab, Juan Pablo (2020)
Non-alcoholic fatty liver disease (NAFLD) currently represents an epidemic worldwide. NAFLD is the most frequently diagnosed chronic liver disease, affecting 20–30% of the general population. Furthermore, its prevalence is predicted to increase exponentially in the next decades, concomitantly with the global epidemic of obesity, type 2 diabetes mellitus (T2DM), and sedentary lifestyle. NAFLD is a clinical syndrome that encompasses a wide spectrum of associated diseases and hepatic complications such as hepatocellular carcinoma (HCC). Moreover, this disease is believed to become the main indication for liver transplantation in the near future. Since NAFLD management represents a growing challenge for primary care physicians, the Asociación Latinoamericana para el Estudio del Hígado (ALEH) has decided to organize this Practice Guidance for the Diagnosis and Treatment of Non-Alcoholic Fatty Liver Disease, written by Latin-American specialists in different clinical areas, and destined to general practitioners, internal medicine specialists, endocrinologists, diabetologists, gastroenterologists, and hepatologists. The main purpose of this document is to improve patient care and awareness of NAFLD. The information provided in this guidance may also be useful in assisting stakeholders in the decision-making process related to NAFLD. Since new evidence is constantly emerging on different aspects of the disease, updates to this guideline will be required in future.